John Dee and the empire of angels: Enochian magick and the occult roots of the modern world (Inner Traditions, 2018)
"A comprehensive look at the life and continuing influence of the 16th-century scientific genius and occultist Dr. John Dee"--

John Dee's occultism: magical exaltation through powerful signs (SUNY series in Western esoteric traditions, ,, 2004)
Description Not Provided

John Dee's natural philosophy: between science and religion (Routledge library editions. Alchemy, 2,, 2013)
Description Not Provided
pt. 1. The propaedeumata aphoristica, 1558 , pt. 2. The monas hieroglyphica, 1564 , pt. 3. The mathematicall praeface, 1570 , pt. 4. The libri mysteriorum, 1583-1589.